Adaptation of BRIAN-interview (Ukranian language version) for biological rhythms assessment at acute psychosis patients - Tarasov, Volodymir; Orlova, Nataliia (Psychosomatic Medicine and General Practice, 2017)
Background. In the last years, the scientific interest in studying human biological rhythms have renewed with the increase in number of publications devoted to people’s “internal rhythms”. For psychological practice, it is necessary to determine the patient’s condition qualitatively and quantitatively. So, we offer an adapted Ukrainian language version of the BRIAN-interview. This is a pilot study, aimed to evaluate general structure, reliability, and validity of the scale and its items. Methods. BRIAN-interview allows assessing the frequency of problems related to the maintenance circadian rhythm regularity in patients with acute psychosis. We have translated English version into Ukrainian and conducted an assessment of the 60 patients with schizophrenia using this scale. Results. During 6 months patients with psychotic disorders (ICD-10 F20-29) and average age 35.2 years were examined in a general psychiatric department. The evaluation was conducted during first 4 days after admission. The total average BRIAN score ranged 41 points. The assessment revealed mild alterations in sleep patterns, daily and social activities, eating habits and chronotype. Determined the clear patterns dependence in different age groups. Conclusion. The results of research for the Ukrainian language BRIAN-interview version among patients with acute psychosis were submitted. Interview evaluates the biological rhythms of the patient in the last 15 days by major domains: sleep, daily and social activity, diet and identify preferred chronotype.